Influences on Motivation and Learning Outcomes in Home Economics: A Pathway to Enhanced TVET Competency Development - David, Sigritch; Zabala, Vanessa; Achondo, Irish; Ruales, Shelanee Theresa (Journal of Technical Education and Training, 2025)
Technical-Vocational Education and Training (TVET) skills are embedded in the basic education curriculum, progressing spirally from basic competencies in elementary and common competencies in Junior High School (JHS) to a more specialized skills in Senior High School (SHS) and beyond. Early competency formation, particularly in Home Economics (HE) is crucial for preparing learners for advanced Technical-Vocational and Livelihood (TVL) specializations, national certification, and career development. As students move through this continuum, motivation becomes a key driver of how foundational skills are acquired and applied. Yet limited empirical research examines how motivation translates into real-life skill use and how this relationship varies across socio-demographic contexts which are essential for designing responsive and contextualized learning strategies. This study investigated the relationship between students’ motivation to learn HE and two outcome indicators: frequency of application (FOA) and self-reported competence (SRC) within the family setting. It also examined the moderating influence of students’ socio-demographic backgrounds. A validated quantitative survey was administered to 200 JHS students. Linear regression tested the associations, while moderation analyses identified contextual variations. Results showed that motivation significantly predicted HE outcomes, with family structure, birth order, family income, and TLE grades moderating the motivation–outcome link, whereas religion, gender, and parents’ occupation did not. These findings offer practical insights for strengthening HE curriculum in JHS by recognizing how motivation and learner contexts shape early competency formation which enhance students’ readiness for SHS TVL coursework and supports smoother progression into higher-level TVET programs and future technical-vocational pathways.